SETTLEMENT PATTERN ANALYSIS KAPUAS RIVERBANK URBAN VILLAGE DALAM BUGIS EAST PONTIANAK SUBDISTRICT - Ikhlas, Muhammad; Azuryan, Azuryan; Pastian, Bibia; Bonaventura, Yolanda; Khoir, Muhammad Thoriqul; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2025)
This research examines settlement patterns along the Kapuas River, particularly in Kelurahan Dalam Bugis, East Pontianak, which is characterized by rapid but unplanned growth. The research objectives include: (1) describe the settlement pattern formed in the area, and (2) identify the factors that influence it. The method used was descriptive qualitative with primary data collection through observation and in-depth interviews, as well as secondary data from literature studies. The results of the analysis show two main patterns: a Linier pattern that follows the path and an organic pattern that develops naturally without a standard spatial layout. Shaping factors include the socio-economic characteristics of the community (port dependency and informal employment), natural conditions (flat topography but affected by waste accumulation), building characteristics (semi-permanent with wooden pile foundations), and infrastructure and accessibility constraints (narrow roads, minimal sanitation and clean water). These settlements also face the risk of flooding, poor sanitation and high density. Therefore, there is a need for integrated spatial planning, legalization of land rights, improvement of basic infrastructure and sustainable environmental management to create safer and more orderly settlements.